CREG1 administration stimulates BAT thermogenesis and improves diet-induced obesity in mice. (14th October 2021) - Kusudo, Tatsuya; Okada, Tadashi; Hashimoto, Michihiro; Takeuchi, Tamaki; Endo, Yuki; Niwa, Ayumi; Yamashita, Hitoshi
Abstract: Brown and beige adipocytes, which express thermogenic uncoupling protein-1 (UCP1), stimulate glucose and lipid metabolism, improving obesity and metabolic diseases such as type 2 diabetes and hyperlipidemia. Overexpression of cellular repressor of E1A-stimulated genes 1 (CREG1) promotes adipose tissue browning and inhibits diet-induced obesity (DIO) in mice. In this study, we investigated the effects of CREG1 administration on DIO inhibition and adipose browning. Subcutaneous administration of recombinant CREG1 protein to C57BL/6 mice stimulated UCP1 expression in interscapular brown adipose tissue (IBAT) and improved DIO, glucose tolerance and fatty liver compared with those in phosphate-buffered saline-treated mice. Injection of Creg1 -expressing adenovirus into inguinal white adipose tissue (IWAT) significantly increased browning and mRNA expression of beige adipocyte marker genes compared with that in mice injected with control virus. The effect of Creg1 induction on beige adipocyte differentiation was supported in primary culture using preadipocytes isolated from IWAT of Creg1-transgenic mice compared with that of wild-type mice. Our results indicate a therapeutic effect of CREG1 on obesity and its associated pathology and a potential of CREG1 to stimulate brown/beige adipocyte formation. Graphical Abstract: